Constipation prevalence and fatigue severity in regular kratom (Mitragyna speciosa Korth.) users. (4th May 2019) - Singh, Darshan; Damodaran, Thenmoly; Prozialeck, Walter C.; Grundmann, Oliver; Karunakaran, Thiruventhan; Vicknasingam, B.
ABSTRACT: Background: User reports suggest that long-term kratom ( Mitragyna speciosa Korth., Rubiaceae) consumption can be associated with negative effects like constipation and withdrawal symptoms such as fatigue. We aim to investigate constipation prevalence from kratom use and fatigue severity during kratom cessation in individuals who reported regular ingestion of kratom decoction. Methods: A total of 125 male regular-kratom users participated in this retrospective study. The Constipation Assessment Scale (CAS) was administered to assess effects during kratom use. The Fatigue Severity Scale (FSS) was used to assess fatigue during kratom withdrawal. Results: All respondents were males, the majority being Malays (97%, n = 121/125). Mean (SD) age was 34 years (11.2), and mean (SD) duration of kratom use was 8.5 years (5.5). A total of 57% had > 6 years kratom use history ( n = 71/125), while 59% ( n = 74/125) had used three or more glasses of kratom tea/juice daily. More than four-fifth (94%, n = 118/125) never experienced constipation; only 6% ( n = 7/125) experienced constipation. As for fatigue, 86% ( n = 108/125) reported fatigue during kratom cessation. Results from chi-square analysis showed that withdrawal from higher (three or more glasses daily) kratom intake was associated with severe fatigue during kratom cessation. Conclusions: Regular and higher (three or more glasses) consumption of kratom decoction did not appear to cause significant constipation problems, but users were prone to severe fatigue during kratom cessation.